Kajian Sosio Historis Hukum Adat dalam Konstitusi Indonesia - M.Misbahul Mujib (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
Indigenous and tribal peoples have recognized in NKRI constitution, UUD 1945. Many factors affect the recognition of indigenous people in the constitution. This study examines the socio-historical factors that influence the recognition of indigenous people in the constitution. This paper uses the legal theories to prove that the law should be born out of history and social reality.